Closure of Iterative Laparotomy in Patients With Previous Mesh Reinforcement a Cohorts’ Study. Short-Term Results - A. Bravo-Salva; A. Bravo-Salva; J.J. Sancho-Insenser; J.J. Sancho-Insenser; M. Pera-Román; M. Pera-Román; J.A. Pereira-Rodriguez; J.A. Pereira-Rodriguez (Journal of Abdominal Wall Surgery, 2022)
Purpose: Due to extension of prophylactic mesh indications use will become more common to find patients receiving an iterative laparotomy (IL) over a previous reinforced abdominal wall. The aim of this study was to analyze outcomes after IL in patients with previous mesh reinforcement.Methods: This study was a prospective secondary analysis of midline laparotomy closure performed from July 2017 to July 2018 registered in PHACPA study (NCT 02658955). IL were included and surgery characteristics and outcomes analyzed. We compared two groups: with (PreM) or without previous prophylactic onlay mesh reinforcement (PreS) Subgroups’ analysis, risk factors for complications and survival free hernia analysis were performed.Results: 121 IL were analyzed. Only obesity was associated with higher SSO (OR 2.6; CI 95% 1.02–6.90; p = 0.04) There were 15 incisional hernias (IH) (14.4%). Group with previous mesh reinforcement (pre M) had a higher statistically significative incidence of IH (OR = 1.21; CI 95% 1.05–1.39; p = 0.015). Use of slowly absorbable suture (OR = 0.74; CI 95% 0.60–0.91; p = 0.001), USP 2/0 suture (OR, 0.31; 95% CI, 0.10–0.94; p = 0.033), and small bites technique (OR = 0.81; CI 95% 0.72–0.90; p = 0.011) were associated with less IH.Conclusion: IL has a high percentage of complications and IH. In case of IL without previous reinforcement, a mesh can help to reduce IH. Our data cannot clearly support any technique to close an IL with previous mesh.